2007
DOI: 10.1172/jci33563
|View full text |Cite
|
Sign up to set email alerts
|

Role for HLA in susceptibility to infectious mononucleosis

Abstract: Factors involved in determining whether infectious mononucleosis occurs after primary EBV infection may include age, dose of virus received, and various genetic markers. A study by McAulay and colleagues reported in this issue of the JCI shows that the presence of certain HLA class I alleles correlates with the incidence and severity of infectious mononucleosis (see the related article beginning on page 3042). These same HLA alleles are also risk factors for EBV-associated Hodgkin lymphoma (HL), supporting rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
(28 reference statements)
0
11
1
Order By: Relevance
“…HLA-A molecules have a central role in the immune system because they are responsible to present and recognize antigens. The study of genetic differences in the HLA locus is important since HLA class 1 alleles may affect viral peptide presentation to T cells, and consequently the effectiveness of the immune response (McAulay et al, 2007;Farrell, 2007). The HLA-A locus A > T (rs2530388) was described as associated with increased risk of infectious mononucleosis (McAulay et al, 2007), nevertheless our data showed no significant associations with NPC development and therefore our results may indicate a different result point of interest regarding possible EBV-association.…”
Section: Hla Locus Snpscontrasting
confidence: 55%
“…HLA-A molecules have a central role in the immune system because they are responsible to present and recognize antigens. The study of genetic differences in the HLA locus is important since HLA class 1 alleles may affect viral peptide presentation to T cells, and consequently the effectiveness of the immune response (McAulay et al, 2007;Farrell, 2007). The HLA-A locus A > T (rs2530388) was described as associated with increased risk of infectious mononucleosis (McAulay et al, 2007), nevertheless our data showed no significant associations with NPC development and therefore our results may indicate a different result point of interest regarding possible EBV-association.…”
Section: Hla Locus Snpscontrasting
confidence: 55%
“…It is one of the most common viral infections of humans, with over 90% of individuals becoming infected at some time during their life [36]. As maternal antibody protection disappears after birth, infants become susceptible to infection by EBV.…”
Section: Introductionmentioning
confidence: 99%
“…EBV is a member of the herpes family of double-stranded linear DNA viruses, which is also referred to as the human herpes virus 4 (or HHV-4). It is one of the most common viral infections of humans, with over 90% of individuals becoming infected at some time during their life [36] . As maternal antibody protection disappears after birth, infants become susceptible to infection by EBV.…”
Section: Introductionmentioning
confidence: 99%
“…The target cell of primary EBV infection is B cells and the symptoms of IM are a result of immune response to the EBV infection, including excessive production of inflamma-tory cytokines by T cells [25]. A genetic contribution to the variability in cytokine secretion in response to antigens has been demonstrated, this could also partially explain a heritable IM susceptibility [26].…”
Section: Discussionmentioning
confidence: 99%